The Effect of Cyber-Ostracism on Social Anxiety Among Undergraduates: The Mediating Effects of Rejection Sensitivity and Rumination - Chun Shi; Peizhen Sun; Jiaru Shi; Haosheng Ye; Junyan Tao (Behavioral Sciences)
In order to examine the relationship between cyber-ostracism and social anxiety among undergraduates, as well as to investigate the mechanisms underlying the effects of cyber-ostracism, rejection sensitivity, and rumination on social anxiety, this study recruited 864 undergraduate students from Jiangsu and Guangdong Provinces in China using a cluster sampling method. The participants completed the Cyber-Ostracism Questionnaire, the Chinese version of the Interaction Anxiousness Scale, the Chinese version of the Rejection Sensitivity Questionnaire, and the Chinese version of the Ruminative Responses Scale. Furthermore, the mediating effects were examined using the structural equation modeling (SEM) method. The results showed that (1) cyber-ostracism was positively related to social anxiety among undergraduates, and (2) rejection sensitivity and rumination played a chain mediating role in the relationship between cyber-ostracism and social anxiety.